No Population Genetic Structure of Skipjack Tuna (Katsuwonus pelamis) in the Tropical Western and Central Pacific Assessed Using Single Nucleotide Polymorphisms - Anderson, Giulia; Lal, Monal; Stockwell, Brian; Hampton, John; Smith, Neville; Nicol, Simon; Rico, Ciro (Frontiers in Marine Science, 2020)
Skipjack tuna (Katsuwonus pelamis) has historically been considered panmictic at the ocean basin scale because of the species’ life history and substantial absolute population size. However, recent advances in population genomics have enabled scientists to demonstrate population structure in other species that were likewise traditionally assumed to be panmictic. Accordingly, we used DArTseq, a proprietary platform of reduced-representation genome sequencing developed by Diversity Arrays Technology (DArTech) to genotype 222 skipjack tuna from 9 sample groups collected across 6 exclusive economic zones (EEZs) and over 6 years in the tropical Western and Central Pacific Ocean. This is one of the most fine-scale population genetics assessments of skipjack tuna to date. We found several statistically significant pairwise FST comparisons using purportedly neutral loci, but very little indication of structure based on observed and expected heterozygosity, effective population size, a Mantel test, AMOVA, numerous genetic clustering and population assignment tests, and exploration of correlation with oceanographic features. Significant pairwise FST values were often shallow and resulted in uncertainty about their biological significance. Furthermore, a test of the hypothesis that the geographic and temporal distribution of the potentially adaptive genetic diversity may depict cryptic fine scale structure using two different outlier detection methods, could not reject panmixia based on estimates of fixation indices and two clustering software. Our results support the presence of a single population of skipjack tuna in the tropical Western and Central Pacific Ocean, but highly recommend the expansion of the study area, in latitude, longitude, and seasonality, before drawing any global conclusions.